Why insurgents kill civilians in capital cities: A disaggregated analysis of mechanisms and trends. (November 2017) - Koren, Ore
Abstract: Research into the causes of violence against civilians has increased significantly in recent years, yet the mechanisms governing spatial patterns of victimization remain poorly understood. My investigation explores if and why one specific locality, capital cities, experiences a higher frequency of violence against civilians perpetrated by armed insurgent organizations. I argue that the political value associated with capitals allows these groups to asymmetrically impose higher costs on the regime by targeting civilians in these localities. I lay out and validate three specific mechanisms to explain this pattern: elite coercion, popular intimidation, and international persuasion. In the first scenario insurgents aim to influence domestic elites directly. In the second, they aim is to affect domestic civilians' resolve. In the third, they seek to influence international audiences. Using new geolocated global atrocities data for the years 1996–2009, I evaluate this linkage by employing different methodological approaches and accounting for potential reporting biases. Finally, I show that ethnic and secessionist wars are more likely to experience atrocities in the capital compared with other conflicts. The findings illustrate potential benefits from explaining the temporal and spatial variation in violence by insurgents, with a focus on strategic conditions and power asymmetries. Highlights: A highly disproportional number of insurgent atrocities occur in capital cities. Relevant mechanisms are identified and empirically validated. Global geospatial analyses confirm this pattern globally. Different conflict types are shown to impact capital atrocities' frequency.